KAJIAN PENGARUH ION Cr(VI) TERHADAP EFEKTIVITAS FOTODEGRADASI 2,4-DINITROFENOL TERKATALISIS TiO2 - Tri Ernawati; Endang Tri Wahyuni; Eko Sugiharto (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2008)
In order to develop a photocatalytic degradation method for removing 2,4-dinitrophenol in the solution, the influence of Cr(VI) ions on the effectiveness of 2,4-dinitrophenol photodegradation catalyzed by TiO2 has been studied. Photodegradation process has been carried out in a closed reactor equipped with UV lamp 40 watt, by irradiating a mixture of 2,4-dinitrophenol solution and TiO2 powder as a photocatalyst, for a period if time accompanied by stirring. In this study, reaction time, concentration of 2,4-dinitrophenol solution and mass of TiO2 have been optimized. Furthermore the influenze of Cr(VI) concentration and solution pH has also been evaluated. The effectiveness is expressed as % 2,4-dinitrophenol was determined by gas chromatography method. The research results showed that increasing mass of TiO2 photocatalyst could improve the effectiveness of photodegradation, but a decrease in the photodegradation was observed hwen further increase of TiO2 mass of added. The effectiveness of photodegradation could also increase as the initial concentration of 2,4-dinitrophenol was increased. When reaction time was extended, photodegradation could improve, but further extent of time gave no different effect. The presence of Cr(VI) ions could enhance the photodegradation, and Cr(VI) ions was reduced simultaneously into Cr(III) ions. The effectiveness further enhanced when the concentrations of Cr(VI) in the solution were increased. Increasing pH from 1 to 7 resulted in the high and same effectiveness of 2,4-dinitrofenol photodegradation , whether absence or presence of Cr(VI) ions, while photodegradation decreased as the pH was increased from 7 to 14. The highest photodegradation, that was 96.60%, of 40 ml 200ppm 2,4-dinitrofenol solution in the presence of 300ppm Cr(VI) ions could be reached when 30 mg TiO2, solution pH 3 and 12 h of reaction time were employed. Further research is suggested to identify in detail the compounds produced from photodegradation.